A relação entre o compartilhamento de conhecimento e o desempenho organizacional, mediada pela capacidade absortiva - Nodari, Felipe (2013)
Knowledge is currently considered a major organizational resource, as it can enable the achievement of competitive advantage, and its management is a challenge for contemporary organizations. The knowledge sharing, defined by the process by which a unit is affected by the knowledge or experience of another unit, is considered one of the main processes of knowledge management, as it can enable improvements in organizational performance by increasing the value of knowledge assets. The knowledge sharing is composed of two processes, the knowledge donation, defined by the communication of the intellectual capital from one individual to another and the knowledge collection, which is the consultation to others to get them to share their intellectual capital. The knowledge sharing may occur both in the intra-organizational level, within the limits of the organization, as the inter-organizational level, with the external environment. The absorptive capacity, defined by the organization's ability to add new knowledge to the pre-existing ones, is proposed as a mediator between knowledge sharing and organizational performance, measured in this work by a benchmarking perspective. Thus, is proposed the following research goal: to determine the relationship of intra and inter-organizational knowledge sharing processes, mediated by absorptive capacity, with organizational performance. The research was conducted in two stages. The first, qualitative, in order to review and evaluate the theoretical model developed from the literature review. At this stage, six experts of knowledge management and business management were consulted through semi-structured interviews, and was used content analysis to process the data. In the next step, in order to validate the research model, the survey method was adopted. The instrument was responded by members of senior management, and was obtained 241 valid questionnaires. The data were analyzed using confirmatory factor analysis, generating a valid measurement model. Further, the structural model was proposed, in order to explain the causal relationships between the constructs. Among the main results, was empirically demonstrated that, mediated by absorptive capacity, the processes of knowledge sharing have positive influence in organizational performance. The mediator role of absorptive capacity between knowledge sharing and organizational performance was confirmed, as well the relationship between intra and inter-organizational sharing and between intra-organizational sharing and performance. Through this work, we developed a measurement model, thus allowing its use in future research about the relationship of the constructs involved, and a structural model, in order to contribute to elucidate variables that have impact in organizational performance. Managerially, this research points to the development of skills related to the recognition and use of sources of knowledge, since it is an ability that, if developed, positively impacts the performance of the organizations, and also to the question that the assets related to knowledge have a greater possibility of generating value if they are shared between individuals and also with the external environment to the organization.